Posted by Jack on October 22, 2002 at 20:09:25:
In Reply to: Implicit Differentiation posted by Gleaming the Cube on October 22, 2002 at 17:08:14:
: Does this look right?
: Find the Derivative and simplify.
: y = (sin^-1 x)^2
: okay...my f(u) = u^2 and u = g(x) = (sin^-1 x)^2
: Using power rule combined with chain rule...
: = 2(sin^-1)du/dx
: = 2(sin^-1)(1/[sqrt (x^2-1)]
: = 2(sin^-1)/[sqrt (x^2-1)] as the solution
: It is correct except for the derivative of arcsin which is 1/sqrt(1-x^2)
Post a Followup